2013
DOI: 10.1007/s11748-013-0337-y
|View full text |Cite
|
Sign up to set email alerts
|

Dual-port thymectomy using subxiphoid approach

Abstract: We have previously reported single-port thymectomy (SPT) through an infrasternal approach, a procedure in which the thymus is removed through a single port. The dual-port thymectomy procedure developed by adding another port to the single-port procedure has eliminated the risk of interference between forceps operated by both hands of the surgeon and has thereby significantly simplified operative procedures. This procedure provides the same operative field as that obtained by median sternotomy and has excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Although the bilateral approach provided adequate exposure of the anterior mediastinum, a higher number of incisions was needed, which may increase operative trauma and postoperative pain (11,17,26,28). Hsu (24,25), Zielinski (18,29,30) and Suda (19,20) reported thoracoscopic thymectomy partially or only via subxiphoid incisions. Hsu CP created a 6-cm semi-curved subxiphoid incision and used the Kent retractor to lift the sternum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the bilateral approach provided adequate exposure of the anterior mediastinum, a higher number of incisions was needed, which may increase operative trauma and postoperative pain (11,17,26,28). Hsu (24,25), Zielinski (18,29,30) and Suda (19,20) reported thoracoscopic thymectomy partially or only via subxiphoid incisions. Hsu CP created a 6-cm semi-curved subxiphoid incision and used the Kent retractor to lift the sternum.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the instruments may interfere with each other. Therefore, they further developed a dual-port thymectomy (19). Although all these approaches provided acceptable view of both sides, there were a few relative shortcomings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Representative examples are the lateral intercostal approach in video-assisted thoracoscopic surgery thymectomy (VATS thymectomy) and robot-assisted thymectomy, cervical incision in transcervical thymectomy and the infrasternal approach [1][2][3][4][5]. Of these, VATS thymectomy is currently the most frequently performed surgical procedure, but it has some drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…good aesthetic outcomes [4]. For surgeons, however, the surgical procedure is technically demanding [5]. We developed this new technique by combining the subxiphoid approach performed through a midline camera port with the use of the da Vinci multijoint robotic system to ensure a clear operative view and improved manoeuvrability as a minimally invasive surgical procedure for patients untreatable with SPT.…”
Section: Videomentioning
confidence: 99%